Ribonucleotide reductase small subunit M2 promotes the proliferation of esophageal squamous cell carcinoma cells via HuR-mediated mRNA stabilization - Jing Zhang; Qiong Wu; Yifei Xie; Feng Li; Huifang Wei; Yanan Jiang; Yan Qiao; Yinhua Li; Yanan Sun; Han Huang; Mengmeng Ge; Dengyun Zhao; et al. (Elsevier, 2024)
Esophageal squamous cell carcinoma (ESCC), a malignancy of the digestive system, is highly prevalent and the primary cause of cancer-related deaths worldwide due to the lack of early diagnostic biomarkers and effective therapeutic targets. Dysregulated ribonucleotide reductase (RNR) expression has been confirmed to be causally linked to tumorigenesis. This study demonstrated that ribonucleotide reductase small subunit M2 (RRM2) is significantly upregulated in ESCC tissue and that its expression is negatively correlated with clinical outcomes. Mechanistically, HuR promotes RRM2 mRNA stabilization by binding to the adenine/uridine (AU)-rich elements (AREs) within the 3'UTR, resulting in persistent overexpression of RRM2. Furthermore, bifonazole is identified as an inhibitor of HuR via computational screening and molecular docking analysis. Bifonazole disrupts HuR-ARE interactions by competitively binding to HuR at F65, R97, I103, and R153 residues, resulting in reduced RRM2 expression. Furthermore, bifonazole exhibited antitumor effects on ESCC patient-derived xenograft (PDX) models by decreasing RRM2 expression and the dNTP pool. In summary, this study reveals the interaction network among HuR, RRM2, and bifonazole and demonstrated that bifonazole is a potential therapeutic compound for ESCC through inhibition of the HuR/RRM2 axis.